Vasectomy Family Planning Policy and the Rights of Social Assistance Recipients: A Critical Study from the Perspective of Ḥifẓ an-Nasl and al-Māl - Nabilah, Deva; Ma’rifah, Aula Nurul; Pranata, Eka Octavian; Puspita, Mega; Gunawan, Hendra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Policies that link access to social assistance with vasectomy reflect a form of state intervention that has the potential to violate basic principles of justice and human rights. Instead of strengthening welfare, such a policy raises serious problems in terms of the protection of offspring (ḥifẓ an-nasl) and the protection of property (al-māl) as stipulated in Maqāṣid as-Sharī'ah. This study uses normative legal approaches and qualitative methods to analyze these policies from the perspective of Islamic ethics and social rights frameworks. The results of the study show that imposing permanent contraceptive methods as a prerequisite for social assistance is not only contrary to the principles of maqāṣid, but also creates systemic discrimination against vulnerable groups. In this context, the state should not necessarily sacrifice the basic rights of citizens for the sake of achieving demographic figures. Therefore, this research challenges policy logic that ignores the values of protection and justice, and encourages the formulation of public policies that are more humane, inclusive, and in accordance with the socio-religious ethics of the Indonesian nation.